Accelerating the utilization of climate-smart agriculture technologies and innovations: How existing policies can foster investment decisions? - Ganyo, Komla Kyky; Kpadonou, Gbedehoue Esaïe; Segnon, Alcade C.; Lamien, Niéyidouba; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This Info Note documents AICCRA engagement and technical assistance to 12 countries in West Africa and the Sahel on how to leverage on existing policies to foster investments for scaling CSA technologies. At least one national policy document on climate change exists in each of the countries. Leveraging on the visions and strategic orientations of these climate policies, relevant CSA technologies and innovations were prioritized. Subsequently, need quantification was made. CSA technologies includes improved crop seeds varieties, livestock breeds, seeding techniques, irrigation technologies, land management practices, and crop protection as well as post-harvest technologies. Pathways for scaling the prioritized technologies included mainly ongoing projects and/or programmes such as FSRP, GIRAV, PROPAD, and projects in pipeline at regional or national levels